A window into the early evolutionary history of Cercopithecidae: Late Miocene evidence from Chad, Central Africa. Issue 132 (July 2019) - Pallas, Laurent; Daver, Guillaume; Mackaye, Hassane T.; Likius, Andossa; Vignaud, Patrick; Guy, Franck
Abstract: Central Africa is known as a major center of diversification for extant Old World Monkeys (OWM) and yet has a poorly documented fossil record of monkeys. Here we report a new colobine monkey ( Cercopithecoides bruneti sp. nov . ) from the Central African hominin-bearing fossiliferous area of Toros-Menalla, Chad at ca . 7 Ma. In addition to filling a gap in the spatial and temporal record of early OWM evolutionary history, we assess the ecomorphological diversity of early OWM by providing evidence on the onset of a folivorous diet and a partial reacquisition of terrestrial locomotor habits among Miocene colobines. We also support the phylogenetic affinities of the genus Cercopithecoides among the stem group of the extant African colobine monkeys.